(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article is devoted to studying the effectiveness of AI-based translators in the educational environment. It examines modern neural network translation systems such as Google Translate, DeepL, Yandex Translate, and GPT-based models, analyzing their capabilities and limitations. The advantages of using AI are discussed, including accelerated access to foreign resources, adaptation of materials to students’ proficiency levels, and support for bilingual learning. Simultaneously, risks and limitations are considered: errors in terminology, context distortions, reduced student autonomy, and pedagogical ethical concerns. The study substantiates the need for critical and controlled use of AI translators and provides recommendations for their integration into the educational process while maintaining education quality and academic standards.